Impact of flood inundation on agriculture land use: a case study in Gua Musang, Kelantan - Ibrahim, Nurliza Azah (2016)
Conventional methods of assessing flood hazard are unable to provide quick, efficient and effective solutions. In recent years, risk based approaches that feature geospatial tools such as remote sensing and geographical information system have been pursued as a viable means to manage flood hazard. Over the past 30 years, floods have been the most tragic natural disaster affecting about 80 million people per year causing economic damage worth over USD11 million annually around the world. Increasing human activity at downstream and upstream of river systems results in greater flood damage in terms of size and frequency. In Malaysia, the National Security Council (NSC) had classified the recent flooding in Kelantan as the worst in the history of the state. Apparently, the water level of the Kelantan River at Tambatan Di Raja, which had a danger level of 25 m, reached 34.2 m in December of 2014 compared to 29.7 m in 2004 and 33.6 m in 1967. Two main reasons for the unusual flooding magnitude are changing climatic patterns and uncontrolled land management and increased exploitation of land resources. This study explore the use of ArcGIS and Digital Elevation Model (DEM) to provide geospatial data to assess flooding effects on agricultural land use in Gua Musang, Kelantan. The changes of agriculture landuse shown clearly in rubber and oil palm plantation as they are the main contributor of agriculture area in study area. Findings from this work provide the necessary benchmark (especially in terms of agricultural land use) for a more comprehensive approach to manage the impact of flood disasters in the near future.